2013
DOI: 10.1002/marc.201300533
|View full text |Cite
|
Sign up to set email alerts
|

From Random Coil Polymers to Helical Structures Induced by Carbon Nanotubes and Supramolecular Interactions

Abstract: A simple method is reported for the preparation of double-helical structures through a series of achiral random and block copolymers poly(styrene-co-4-vinylbenzyl triazolylmethyl methylthymine) (PS-co-PVBT) with various T units on the side chains through click reactions of poly(styrene-co-4-vinylbenzyl azide) (PS-co-PVBN(3)) with propargyl thymine (PT) and also the synthesis of the A-appended pyrene derivative (A-Py) through click chemistry. This double-helical structure is observed from achiral random-coil po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
22
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 44 publications
1
22
0
Order By: Relevance
“…There is much interest in supramolecular structures based on complementary multiple-hydrogen-bond arrays prepared from synthetic polymers presenting nucleotide bases on their side chains [21][22][23][24][25][26][27][28][29][30][31][32][33][34]. The binding forces in systems featuring multiple hydrogen bonds can be tuned, leading to inter-association equilibrium constants (K A ) ranging from several hundred up to more than 10 6 [21][22][23][24][25][26][27][28][29][30][31][32][33][34].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is much interest in supramolecular structures based on complementary multiple-hydrogen-bond arrays prepared from synthetic polymers presenting nucleotide bases on their side chains [21][22][23][24][25][26][27][28][29][30][31][32][33][34]. The binding forces in systems featuring multiple hydrogen bonds can be tuned, leading to inter-association equilibrium constants (K A ) ranging from several hundred up to more than 10 6 [21][22][23][24][25][26][27][28][29][30][31][32][33][34].…”
Section: Introductionmentioning
confidence: 99%
“…The binding forces in systems featuring multiple hydrogen bonds can be tuned, leading to inter-association equilibrium constants (K A ) ranging from several hundred up to more than 10 6 [21][22][23][24][25][26][27][28][29][30][31][32][33][34]. The most important arrays of multiple hydrogen bonding interactions are those found in complex biological systems, for example, DNA, a very influential structure in polymer science that is often presented as a defined macromolecule possessing a nearly perfect molecular structure.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the presence of CNTs in, for example, semicrystalline polymeric 37,38 and biopolymeric 39,40 matrices favours the crystallization of the latter around CNTs. Typically, X-ray diffraction (XRD) experiments performed with the composites reveal d-spacings of the matrix components, which suggests that the incorporation of CNTs into polymer matrices does not provoke sudden changes in the internal structures of the latter.…”
mentioning
confidence: 99%
“…Adenine, thymine, propargyl bromide, and K2CO3 were obtained from Showa Chemical (Tokyo, Japan). 1-Hydroxy-2-phenyl-2-(2′,2′,6′,6′-tetramethyl-1-piperidinyloxy)ethane (TEMPO-OH), PA, PT, poly(vinylbenzyl chloride) (PVBC) (Scheme 1a), poly(vinylbenzyl azide) (PVBN3) (Scheme 1b), and poly(vinylbenzyl triazolylmethyl methylthymine) (PVBT) (Scheme 1c) were prepared according to procedures described previously [21,29,56,58,60]. All solvents and other chemicals were used as received.…”
Section: Methodsmentioning
confidence: 99%
“…We have also studied the application of multiple hydrogen bonds in modifying the miscibility behavior and supramolecular structures of several nucleobase-functionalized polymers prepared through free radical polymerization [52][53][54][55][56][57][58][59][60][61][62][63][64][65][66]. We found that the preparation of highly A-or T-functionalized vinylbenzyl monomers can be difficult, due to the polarities of these hetero-nucleobase monomers being significantly different from those of typical commercial monomers (e.g., methacrylate or styrene monomers) [52][53][54].…”
Section: Introductionmentioning
confidence: 99%